Pengaruh Ketersediaan Air dan Interval Waktu Pemberian Mulsa terhadap Pertumbuhan dan Perkembangan Tanaman Padi Gogo - Yakup, Yakup; Sefrila, Marlin (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Yakup, Y., Sefrila, M. (2024). The effects of water supplies and mulching intervals on growth and development of upland rice. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 305–312). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Water availability is one of the factors that can influence the productivity of upland rice, so the use of mulch is an alternative that can be applied because applying mulch at certain time intervals can suppress evaporation and support groundwater availability. This research aimed to determine the effect of water provision and mulch application intervals on the growth and development of upland rice. The experiment used a randomized complete block design with two factors and 3 replications.The first factor were water supplies when showed by proportion of field capacity (FC) in some weeks after planting (WAP), i.e. : FC (since 0 WAP); 4/5 FC (0 WAP) and FC (since 2 WAP); 3/5 FC (0 WAP), 4/5 FC (2 WAP), and FC (since 4 WAP); 2/5 FC (0 WAP), 3/5 FC (2 WAP), 4/5 FC (4 WAP), FC (since 6 WAP). The second factor were mulching intervals, i.e.: 0 – 2 WAP; 0 – 4 WAP; and 0 – 6 WAP. The Observations included plant height (2, 4, and 6 WAP), and number of tillers (6 WAP). The results showed that water supply 3/5 FC (0 – 4 WAP) still could be tolerated by early growth of upland rice, but water supply 2/5 FC (0 – 2 WAP) decreased early growth of upland rice significantly. Mulching interval since planting to 4 and 6 weeks after planting able to increased tillers number, while the mulching interval since planting to 2 weeks after planting had no significantly effect on tillers number of upland rice.